1999
DOI: 10.1046/j.1462-2920.1999.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity of termite gut spirochaetes

Abstract: A molecular phylogenetic analysis was done of not-yet-cultured spirochaetes inhabiting the gut of the termite, Reticulitermes flavipes (Kollar). Ninety-eight clones of near-full-length spirochaetal 16S rDNA genes were classified by ARDRA pattern and by partial sequencing. All clones grouped within the genus Treponema, and at least 21 new species of Treponema were recognized within R. flavipes alone. Analysis of 190 additional clones from guts of Coptotermes formosanus Shiraki and Zootermopsis angusticollis (Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(114 citation statements)
references
References 59 publications
8
106
0
Order By: Relevance
“…Delta-proteobacteria have been recognised as playing a major role in the H 2 +CO 2 economy of termite hindgut communities; nitrogen-fixing Desulfovibrio strains have been isolated from the gut of termites (Ohkuma et al 1996;Sato et al 2009). Spirochaetes are a major constituent of wood-feeding termite gut microbiota (Lilburn et al 1999;Leadbetter et al 1999), both in lower (Yang et al 2005) and higher termites (Paster et al 1996;Warnecke et al 2007). In contrast, the population of Spirochaetes in the gut of fungus-growing and soil-feeding termites is lower SchmittWagner et al 2003) or absent (Shinzato et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Delta-proteobacteria have been recognised as playing a major role in the H 2 +CO 2 economy of termite hindgut communities; nitrogen-fixing Desulfovibrio strains have been isolated from the gut of termites (Ohkuma et al 1996;Sato et al 2009). Spirochaetes are a major constituent of wood-feeding termite gut microbiota (Lilburn et al 1999;Leadbetter et al 1999), both in lower (Yang et al 2005) and higher termites (Paster et al 1996;Warnecke et al 2007). In contrast, the population of Spirochaetes in the gut of fungus-growing and soil-feeding termites is lower SchmittWagner et al 2003) or absent (Shinzato et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The taxonomic compositions of gut bacteria have been examined in various termite species by 16S rRNA clone analysis (Table 1). 7,8,[20][21][22][23][24][25][26][27][28][29][30][31][32] More than 1,500 phylotypes in total (with a criterion of >97% sequence identity in near-full length 16S sequence) have been obtained to date, most of which have never been detected in other environments and show low sequence similarities to cultured bacterial strains. In both lower and higher termites, it has been estimated that a single termite species harbors several hundred or more gut bacterial phylotypes.…”
Section: Diversity Of Termite Gut Symbiontsmentioning
confidence: 99%
“…Spirochaetes exist in several environments (Choi et al, 1997;Iida et al, 2000;Lilburn et al, 1999;Paster et al, 1996) in addition to the human oral cavity. Furthermore, a number of spirochaetes are present in termite guts (Lilburn et al, 1999).…”
Section: Computer-simulated T-rflp Analysismentioning
confidence: 99%
“…Lilburn et al (1999) reported that at least 21 new species of Treponema were recognized within one termite species. In our study, 194 treponemal sequences (including termite-gut spirochaetal clones) retrieved from the DDBJ/ EMBL/GenBank were selected for the T-RFLP analysis.…”
Section: Computer-simulated T-rflp Analysismentioning
confidence: 99%
See 1 more Smart Citation